2009
DOI: 10.1104/pp.109.135780
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Photooxidation-Induced Transcriptome Reprogramming in ArabidopsisimmutansWhite Leaf Sectors    

Abstract: Arabidopsis (Arabidopsis thaliana) immutans (im) has green and white sectoring due to the action of a nuclear recessive gene, IMMUTANS. The green sectors contain normal-appearing chloroplasts, whereas the white sectors contain abnormal chloroplasts that lack colored carotenoids due to a defect in phytoene desaturase activity. Previous biochemical and molecular characterizations of the green leaf sectors revealed alterations suggestive of a source-sink relationship between the green and white sectors of im. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
105
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 92 publications
18
105
0
1
Order By: Relevance
“…By contrast, the meta-analysis revealed that IM did appear to be strongly regulated by development in Arabidopsis (Rosso et al, 2006). This is consistent with the observations of Aluru et al (2001Aluru et al ( , 2009 who suggested that IM is required to protect against the potential for photooxidation during the development of chloroplasts, amyloplasts, and etioplasts. Wu et al (1999) proposed that the presence of white sectors in im plants occurs because IM plays a critical role in carotenoid biosynthesis due to its ability to oxidize the PQ pool.…”
Section: Introductionsupporting
confidence: 87%
See 4 more Smart Citations
“…By contrast, the meta-analysis revealed that IM did appear to be strongly regulated by development in Arabidopsis (Rosso et al, 2006). This is consistent with the observations of Aluru et al (2001Aluru et al ( , 2009 who suggested that IM is required to protect against the potential for photooxidation during the development of chloroplasts, amyloplasts, and etioplasts. Wu et al (1999) proposed that the presence of white sectors in im plants occurs because IM plays a critical role in carotenoid biosynthesis due to its ability to oxidize the PQ pool.…”
Section: Introductionsupporting
confidence: 87%
“…If the PQ pool remains reduced due to the lack of IM, carotenoid biosynthesis is blocked at the phytoene desaturase step, phytoene accumulates, and photobleaching results from an increase in chloroplastic ROS (Wetzel et al, 1994;Wu et al, 1999). Consistent with the notion that white sectoring is triggered by photooxidation (Aluru et al, 2009) is the fact that the variegated phenotype can be suppressed in im plants when grown under low-light conditions (Ré dei, 1963;Wetzel et al, 1994;Aluru and Rodermel, 2004;Rosso et al, 2006).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations